The economic value of landscapes - Heide, C. Martijn van der.; Heijman, Willem (New York : Routledge, 2013)
"This book aims to explore the avenue of landscape economics and provides the building blocks (from different scientific disciplines) for an economic analysis of landscapes. What exactly constitutes and determines the value of a landscape? It focuses on the value of landscapes in its broadest sense, thereby covering a variety of topics including stakeholder involvement in landscape design, landscape governance and landscape perceptions from different countries. Merely saying that landscapes have value or are important is not sufficient - not when resources are scarce and have alternative uses. Measuring and quantifying the economic value of changes in landscapes would help ensure that landscape management decisions are both (economically) rational and sound"--
pt. I. Rise to the challenge : an awakening to awareness -- pt. II. Reorientations and reflections : building blocks of landscape economics -- pt. III. Worldwide applications and detailed case studies : integration of practices -- pt. IV. Outlook for landscape economics : burgeoning perspectives on recreation, agriculture and urban agglomeration.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Landscape design -- Economic aspects; Real estate development; Value added; Electronic books